Un modèle-outil pour représenter le savoir technopédagogique disciplinaire des enseignants - Sylviane Bachy
The new Technopedagogical Disciplinary Knowledge model that we propose integrates different dimensions: discipline (D), personal epistemology (E), pedagogical knowledge (P) and technology knowledge (T). We acknowledge the existence of relationships between the components of the model that can be more or less strong according to the profiles of teachers. All these dimensions are present in teachers' profiles, but they do not have the same importance. In order to establish the different profiles of teachers we designed a questionnaire to test the component and the relationships. The questionnaire was submitted a first time in order to check if the items were understandable and if the profiles that emerged were reliable based on what we knew of and about the teachers. A second test was carried out based on comparing the answers of university and non-university teachers. The purpose was to test the consistency between groups of items and the correlations between the different dimensions of the model. It appears that the "pedagogical knowledge" dimension is significantly correlated with the other three dimensions (technological knowledge, personal epistemology and discipline). This consolidated framework has help build up education development coaching in teaching practices that imply technology.